Assessing the effect of different shapes of glyco-gold nanoparticles on bacterial adhesion and infections - Chaudhary, Preeti Madhukar; Sangabathuni, Sivakoti; Murthy, Raghavendra Vasudeva; Paul, Ajay; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemical Communications, 2015)
Achieving selective and sensitive carbohydrate-protein interactions (CPIs) using nanotechnology is an intriguing area of research. Here we demonstrate that the different shapes of gold nanoparticles (AuNPs) functionalized with monosaccharides tune the bacterial aggregations. The mechanism of aggregation revealed that the large number of surface interactions of rod shaped mannose-AuNPs with E. coli ORN 178 compared with spherical and star-shaped AuNPs exhibited higher avidity and sensitivity. Moreover, such sensitive binding can be used for effective inhibition of bacterial infection of cells.

Immobilization of multivalent glycoprobes on gold surfaces for sensing proteins and macrophages - Gade, Madhuri; Khandelwal, Puneet; Sangabathuni, Sivakoti; Bavireddi, Harikrishna; Murthy, Raghavendra Vasudeva; Poddar, Pankaj; Kikkeri, Raghavendra (Analyst, 2016)
The multivalent display of carbohydrates on the cell surface provides cooperative binding to improve the specific biological events. In addition to multivalency, the spatial arrangement and orientation of sugars with respect to external stimuli also trigger carbohydrate-protein interactions. Herein, we report a non-covalent host-guest strategy to immobilize heptavalent glyco-beta-cyclodextrin on gold-coated glass slides to study multivalent carbohydrate-protein interactions. We have found that the localization of sugar entities on surfaces using beta-cyclodextrin (beta-CD) chemistry increased the avidity of carbohydrate-protein and carbohydrate-macrophage interactions compared to monovalent-beta-CD sugar coated surfaces. This platform is expected to be a promising tool to amplify the avidity of sugar-mediated interactions on surfaces and contribute to the development of next generation bio-medical products.